2020
DOI: 10.1007/s00339-020-03489-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties, martensitic and magnetostructural transformations of ferromagnetic Ni–Mn–Sn–Cu shape memory alloys

Abstract: The influence of Cu doping on structural and magnetic properties of Ni50-xMn36Sn14-yCux, y (x=0, 1,2 and y=1 at. %) ribbons has been investigated. The crystalline structures of the alloys were resolute by X-ray diffraction (XRD). It is found that the addition of Cu for Ni stabilizes austenite phase, whereas, replacing small amount of Cu for Sn stabilizes modulated martensite phase. Differential scanning calorimetry measurements have proved the characteristic transformation temperatures. The transformation temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…By this melt spinning technique, ribbon-flake samples were obtained. Additional information about processing and analysis can be found in references [3,4,11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By this melt spinning technique, ribbon-flake samples were obtained. Additional information about processing and analysis can be found in references [3,4,11].…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the addition of a fourth element to Ni-Mn-Sn systems is a current strategy to tune the structural-magnetic transformations and the magnetic behaviour of SMAs, enhancing the properties even though it can also modify the structure [10]. Numerous quaternary systems have been established, such as those with the addition of Cu [11], Co [12], Fe [13], W [14] or Pd [15]. The additions usually produce a shift of the transformation temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An applied magnetic field leads to stabilization of the high-temperature austenite phase. Difference between Zeeman energy of austenite phase and that of martensite phase causes a large change in magnetization during the martensitic transition which is evidence of a field-induced martensitic transformation (FIMT) [9]. A large entropy change and a good magnetocaloric effect occur due to the large magnetization change.…”
Section: Introductionmentioning
confidence: 99%
“…In order to shift the T M temperatures and to reduce the degree of hysteresis associated with the structural martensitic transition, some elements, such as Co, Cu and Pd, have been substituted/doped to the off-stoichiometric Ni-Mn-Sn system [9,[19][20][21]. It was found that Cu substitution has significant effects on the properties of the Ni-Mn-Sn system; the Cu substitution for Mn and Sn caused a shift of the martensitic transition to high temperatures [7,9,22,23], while the transition with the Cu substitution for Ni shifted to low temperatures [24,25]. Since Cu is non-magnetic, the exchange interactions in the system reduce and thus Curie temperature shifts to low temperatures.…”
Section: Introductionmentioning
confidence: 99%